Dye removal from aqueous solution by using adsorption on treated sugarcane bagasse - Saad, Saiful Azhar; Abdullah, Abdul Ghani Liew; Daud, Suhardy; Kasim, Farizul Hafiz; Mohamed Dzahir, Mohd Irfan Hatim (Science Publications, 2005)
The use of cheap and ecofriendly adsorbents has been studied as an alternative substitution of activated carbon for the removal dyes from wastewater. Adsorbents prepared from sugarcane baggase-an agro industries waste was successfully used to remove the methyl red from an aqueous solution in a batch reactor. This study investigates the potential use of sugarcane baggase, pretreated with formaldehyde (PCSB) and sulphuric acid (PCSBC), for the removal of methyl red from simulated wastewater. Formaldehyde treated and sulphuric acid treated sugarcane bagasse were used to adsorb methyl red at varying dye concentration, adsorbent dosage, pH and contact time. Similar experiment was conducted with commercially available powdered activated carbon (PAC), in order to evaluate the performance of PCSB and PCSBC. The adsorption efficiency of different adsorbents was in the order PAC>PCSBC>PCSB. The initial pH of 6-10 flavors the adsorption of both PCSB and PCSBC. Adsorbents are very efficient in decolorized diluted solution. It is proposed that PCSB and PCSBC, in a batch or stirred tank reactors could be employed as a low cost alternative in wastewater treatment for the dye removal.